ByzRev 07.2025.029: Georgios Theotokis, The Art of War in Byzantium: (Past Imperfect). Leeds: Arc Humanities Press 2024. - Kyriakidis, Savvas (The Byzantine Review, 2025)
Georgios Theotokis, The Art of War in Byzantium (Past Imperfect). Leeds: Arc Humanities Press 2024. 134 pp. – ISBN 978-1-80270-100-5